Respuesta :
Answer:
(5,2)
Step-by-step explanation:
Multiply equation to get like terms
Use elimination
Solve for x and y
Answer:
(5, -2)
Explanation:
Step 1 - Align the system of equations and multiply the first equation by 3 and the second row by 4
4x - 3y = 26
3x + 2y = 11
12x - 9y = 78
12x + 8y = 44
Step 2 - Subtract
12x - 9y = 78
12x + 8y = 44
-17y = 34
Step 3 - Simplify by dividing both sides of the equation by -17
-17y = 34
-17y/ -17 = 34/ -17
y = -2
So, y = -2
Step 4 - Enter the value of y into one of the equations and simplify
12x - 9y = 78
12x - 9(-2) = 78
12x - (-18) = 78
12x + 18 = 78
Step 5 - Subtract 18 from both sides
12x + 18 = 78
12x + 18 - 18 = 78 - 18
12x = 60
Step 6 - Divide both sides by 12
12x = 60
12x/ 12 = 60/ 12
x = 5
So, x = 5
(5, -2)
Explanation:
Step 1 - Align the system of equations and multiply the first equation by 3 and the second row by 4
4x - 3y = 26
3x + 2y = 11
12x - 9y = 78
12x + 8y = 44
Step 2 - Subtract
12x - 9y = 78
12x + 8y = 44
-17y = 34
Step 3 - Simplify by dividing both sides of the equation by -17
-17y = 34
-17y/ -17 = 34/ -17
y = -2
So, y = -2
Step 4 - Enter the value of y into one of the equations and simplify
12x - 9y = 78
12x - 9(-2) = 78
12x - (-18) = 78
12x + 18 = 78
Step 5 - Subtract 18 from both sides
12x + 18 = 78
12x + 18 - 18 = 78 - 18
12x = 60
Step 6 - Divide both sides by 12
12x = 60
12x/ 12 = 60/ 12
x = 5
So, x = 5